2008
DOI: 10.1098/rstb.2008.0026
|View full text |Cite
|
Sign up to set email alerts
|

Daphniahybridization along ecological gradients in pelagic environments: the potential for the presence of hybrid zones in plankton

Abstract: The relative homogeneity of pelagic environments has been regarded as the reason for the absence of hybrid zones for hybridizing planktonic Daphnia (Crustacea: Cladocera); occasional dominance of interspecific hybrids over parental species was explained by their temporal superiority in fluctuating environments. However, water bodies with spatially varying environmental conditions might facilitate the formation of hybrid zones in plankton. We studied the distribution of species and hybrids of the Daphnia longis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 40 publications
2
73
0
Order By: Relevance
“…Allozymes, microsatellites, and ITS-RFLP analyses split the data set into five taxa: D. galeata, D. longispina, D. cucullata, D. galeata 9 longispina hybrids, and D. galeata 9 cucullata hybrids. No individual representing a D. longispina 9 cucullata hybrid was present in the data set (see also Petrusek et al, 2008b). In general, the molecular markers corresponded well to each other ( Table 2).…”
Section: Molecular Markersmentioning
confidence: 60%
See 4 more Smart Citations
“…Allozymes, microsatellites, and ITS-RFLP analyses split the data set into five taxa: D. galeata, D. longispina, D. cucullata, D. galeata 9 longispina hybrids, and D. galeata 9 cucullata hybrids. No individual representing a D. longispina 9 cucullata hybrid was present in the data set (see also Petrusek et al, 2008b). In general, the molecular markers corresponded well to each other ( Table 2).…”
Section: Molecular Markersmentioning
confidence: 60%
“…In studies on hybridizing Daphnia, it is even more crucial, as some mismatch of the markers can be expected (Schwenk & Spaak, 1995). In our previous studies of the D. longispina complex Petrusek et al, 2008b), we showed that unexpected intraspecific variation may substantially influence the interpretation of restriction patterns from ITS-RFLP (Billiones et al, 2004). As no detailed study has directly compared results of various molecular approaches for taxon identification in this species complex so far, the real extent of these discrepancies remains unknown.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations